(untitled) (Interdisciplinary Studies Journal, 2025)
Cooperativism has emerged as an important means of building alternatives for the commercialization of products from peasant family units in northeastern Pará. Thus, this article aims to gather information on the cooperativism developed by family (peasant) agriculture in Northeastern Pará (NEP) and to list the cooperatives established in this region. The methodology used was bibliographic research, collecting data from theses, dissertations, articles, and documents focused on peasant cooperativism in Northeastern Pará. The keywords used were: "cooperativism," "Northeastern Pará," "cooperatives," and "solidarity economy," either combined or used individually. A total of 197 cooperatives were identified in the northeastern region of Pará, of which 54 are located in the Guamá microregion, 20 in Bragantina, 75 in Cametá, 28 in Salgado, and 20 in the Tomé-Açu microregion.